Harnessing the potential for otolith microchemistry to foster the conservation of Amazonian fishes. Issue 5 (25th March 2021) - Hermann, Theodore W.; Duponchelle, Fabrice; Castello, Leandro; Limburg, Karin E.; Pereira, Luciana A.; Hauser, Marília
Abstract: Freshwater environments host roughly half of the world's fish diversity, much of which is concentrated in large, tropical river systems such as the Amazon. Fishes are critical to ecosystem functioning in the Amazon River basin but face increasing human threats. The basic biology of these species, and particularly migratory behaviour, remains poorly studied, in part owing to the difficulty associated with conducting tagging studies in remote tropical regions. Otolith microchemistry can circumvent logistical issues and is an increasingly important tool for studying fish life histories. However, this approach is still new in the Amazon, and its potential and limitations to inform fish conservation strategies remain unclear. Here, otolith microchemistry studies in the Amazon are reviewed, highlighting current possibilities, and several key factors that limit its use as a conservation tool in the Amazon are discussed. These include the dearth of spatiotemporal elemental data, poor understanding of environment–fish–otolith pathways, and insufficient funding, facilities, and equipment. A research initiative is proposed to harness the potential of this technique to support conservation in the Amazon. Key aspects of the proposal include recommendations for internal and external funding, which are critical to acquiring and maintaining technical staff, cutting‐edge equipment, and facilities, as well as fostering regular scientific meetings and working groups. Meetings can facilitate a systematic approach to investigating environment–otolith pathways, broadening the chemical baseline for most Amazonian tributaries, and exploring potential valuable elements. These outcomes are urgently needed to conserve biodiversity and ecosystem functioning in the Amazon, especially given threats such as widespread hydroelectric damming. The initiative proposed here could make otolith microchemistry an important, cost‐effective tool to inform and foster conservation in the Amazon, and act as a template for other imperilled tropical river basins, such as the Mekong and the Congo.